A study on the relationship between perceived CSR motives, authenticity and company attitudes: a comparative analysis of cause promotion and cause-related marketing - Min Ah Jeon; Daechun An (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
In order to delve into the complexity involved in the role of authenticity in the context of CSR marketing, this study examines the relationships among perceived CSR motives, authenticity and company attitudes. A different effect of perceived CSR motives on authenticity is also examined between the two most representative types of CSR activities, namely, cause promotion and cause-related marketing. The results from a face-to-face survey with a sample of 289 respondents show that value-driven and stakeholder-driven motives had a positive effect on CSR authenticity while egoistic motives negatively affected CSR authenticity. Also, the effects of value-driven and stakeholder-driven motives on CSR authenticity were found to be larger for cause promotion than they were for cause-related marketing. However, the difference in the effects of the other two motives on CSR authenticity was not statistically significant between cause promotion and cause-related marketing. In addition, the effect of CSR authenticity on company attitudes was found to be statistically significant. When the relative strengths of the effects of four categories of motives on CSR authenticity were compared, value-driven motives had the strongest effect on CSR authenticity for both cause promotion and cause-related marketing. Interestingly, for cause promotion, stakeholder-driven motives had the second strongest effect while egoistic motives were least influential. For cause-related marketing, egoistic motives were found to be the second most influential factor, followed by strategic and stakeholder-driven motives. Practical implications of these finding are discussed along with theoretical implications.
Keywords: 650; CSR motives; Authenticity; Cause promotion; Cause-related marketing; Company attitudes